Social movements, stakeholders and non-market strategy - Briscoe, Forrest; King, Brayden G.; Leitzinger, Jocelyn (Research in the sociology of organizations, 2018)
This volume brings together new research that bridges the domains of stakeholder theory, non-market strategy and social movement theory. Although these three research domains have developed via relatively distinct academic communities, they speak to a common set of phenomena at the intersection of business, markets, civil society, and the state. This collection sets an agenda for a more holistic theory of business and society a theory that takes seriously the various kinds of stakeholders that make up society and have claims over business, that incorporates the goals and objectives of businesses to survive and thrive, and that places an important role on the process of mobilization and contentious interaction between actors whose goals inherently conflict.Using a range of quantitative and qualitative methods, contributors focus on a phenomenon at the intersection of business, civil society, and government. Examining markets shaped by heavy stakeholder involvement and contention, chapters explore topics such as markets for electric vehicles, medical marijuana, municipal drinking water, and cigarettes along with controversial business practice, including employment practices for LGBT workers and racial/ethnic minorities, and working conditions in global supply chains.